Severe infections after allogeneic peripheral blood stem cell transplantation: a matched-pair comparison of unmanipulated and CD34+ cell-selected transplantation - R Martino; M Rovira; E Carreras; C Solano; S Jorge; J De La Rubia; MD Caballero; JP de Oteyza; J Zuazu; JM Moraleda; E Ojeda; C Ferra; et al. (Haematologica, 2001)
BACKGROUND AND OBJECTIVES: T-cell depletion of the graft delays immune recovery following allogeneic peripheral blood stem cell transplantation (PBSCT), but it is not clear whether it actually increases the risk of severe infections after the transplant. DESIGN AND METHODS: We have compared the occurrence of severe infections following 162 CD34+ cell-selected allogeneic PBSCT and 162 unmanipulated PBSCT (CD34+ and UM groups, respectively) from HLA-identical siblings. RESULTS: The probability of infection-related mortality (IRM) was 22% in the UM group and 31% in the CD34+ group (log-rank, p=0.2). In multivariate analyses only the use of fluconazole prophylaxis showed a protective effect on IRM in the whole set of patients, while in both transplant groups the most significant factor was the development of moderate-to-severe graft-versus-host disease (GVHD). The probability of developing cytomegalovirus (CMV) infection was 42% in the UM group and 59% in the CD34+ group (p=0.002), with no differences in CMV disease (10% and 9%, respectively). Multivariate analysis of CMV infection identified three variables associated with a higher risk in the whole set of patients: CMV positive serostatus, CD34+ transplant group and recipient age above 40 years. The development of moderate-to-severe GVHD was a significant factor only in the UM group. Disseminated varicella-zoster virus infection was more common in the CD34+ group (19% and 12%, p=0.05), as were early (< 30 days post-transplant) severe bacterial infections (28% vs 14%, p=0.002). Invasive fungal infections and pneumonias of unknown origin did not differ between groups. INTERPRETATION AND CONCLUSIONS: Our results do not show a significant increase in the risk of dying from an opportunistic infection with CD34+-PBSCT, but the risk of CMV infection is increased, with no differences in CMV disease or mortality attributable to CMV. There is an additive effect on IRM of developing moderate-to-severe GVHD (acute or chronic) following CD34+-PBSCT, and in this subset of patients maximum efforts for the prevention and early treatment of opportunistic infections should be pursued.